2015
DOI: 10.1371/journal.pbio.1002069
|View full text |Cite
|
Sign up to set email alerts
|

Luminal Progenitors Restrict Their Lineage Potential during Mammary Gland Development

Abstract: The hierarchical relationships between stem cells and progenitors that guide mammary gland morphogenesis are still poorly defined. While multipotent basal stem cells have been found within the myoepithelial compartment, the in vivo lineage potential of luminal progenitors is unclear. Here we used the expression of the Notch1 receptor, previously implicated in mammary gland development and tumorigenesis, to elucidate the hierarchical organization of mammary stem/progenitor cells by lineage tracing. We found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
130
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(144 citation statements)
references
References 38 publications
(63 reference statements)
13
130
1
Order By: Relevance
“…Using this method, we showed that the Cre used to support multipotency during MG development and homeostasis, although preferentially labeling BCs, also initially and independently labeled some LCs, as evidenced by the presence of isolated marked LCs just after Cre-mediated recombination and the fact that the frequency of these unicolor doublets was not statistically enriched over bicolor doublets. The frequency of these events corresponds to what would be observed by chance if the Cre were labeling two neighboring cells, further suggesting that MG development and adult remodeling are not mediated by multipotent SCs but rather by two independent lineages (Van Keymeulen et al 2011;Lafkas et al 2013;Prater et al 2014;Tao et al 2014;Rodilla et al 2015). Different transgenic mice using a similar human K14 promoter fragment lead to very different targeting efficiency and specificity of labeling in the MG.…”
Section: Inferring Multipotency From Multicolor Lineage Tracing Expermentioning
confidence: 54%
See 4 more Smart Citations
“…Using this method, we showed that the Cre used to support multipotency during MG development and homeostasis, although preferentially labeling BCs, also initially and independently labeled some LCs, as evidenced by the presence of isolated marked LCs just after Cre-mediated recombination and the fact that the frequency of these unicolor doublets was not statistically enriched over bicolor doublets. The frequency of these events corresponds to what would be observed by chance if the Cre were labeling two neighboring cells, further suggesting that MG development and adult remodeling are not mediated by multipotent SCs but rather by two independent lineages (Van Keymeulen et al 2011;Lafkas et al 2013;Prater et al 2014;Tao et al 2014;Rodilla et al 2015). Different transgenic mice using a similar human K14 promoter fragment lead to very different targeting efficiency and specificity of labeling in the MG.…”
Section: Inferring Multipotency From Multicolor Lineage Tracing Expermentioning
confidence: 54%
“…These two tissues present interesting similarities. They both originate from multipotent embryonic progenitors, which are replaced in adult tissue by unipotent basal and luminal SCs (Van Keymeulen et al 2011;Choi et al 2012;Ousset et al 2012;Wang et al 2013;Prater et al 2014;Rodilla et al 2015). The main difference between the prostate and the mammary BCs is the timing of the switch from multipotency to unipotency.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations